(SOME) COURTS ARE LOOKING FOR NEW APPROACHES AND PRINCIPLES OF ENVIRONMENTAL AND NATURE PROTECTION - Knez, Rajko (Glasnik Advokatske komore Vojvodine, 2025)
Abstract: Environmental degradation is escalating at a pace that is outpacing the capacity of traditional legal responses. Drawing on recent jurisprudence, this paper argues that courts are beginning to bridge the gap left by hesitant legislatures and executives by importing soft-law norms, reviving the precautionary principle, and embracing intergenerational responsibility. Administrative law thus becomes a frontline instrument: buffer zones around drinking-water sources, for instance, now hinge on future rather than present risk. By contrast, criminal law remains shackled to “blanket” norms that condition liability on the breach of narrowly framed environmental regulations, leaving serious violations, such as pollution caused by a traffic accident, outside its reach. The author contends that without a results-oriented reinterpretation of environmental crimes, the promise of Directive 2008/99/EC and its 2024 successor will remain unfulfilled. Only a coordinated evolution of administrative, private, and criminal mechanisms can restore the law’s deterrent force and safeguard environmental integrity for future generations.
Keywords: environmental protection; administrative law; criminal law; precautionary principle; intergenerational responsibility; EU Environmental Crime Directive